AKTIVITAS METAKOGNITIF SISWA DALAM MEMECAHKAN MASALAH BANGUN RUANG SISI DATAR - Suci Zuhriati; Cholis Sa'dijah; Sisworo Sisworo (FMIPA UNIVERSITAS NEGERI MALANG, 2021)
Metacognition is an important aspect in problem solving. This study aims to describe the students' metacognitive activity in solving the problem of building a flat side with a qualitative approach. The research subjects were three students of MTSN Malang 1 with good communication skills in the categories of high, medium, and low mathematical abilities. Data collection was done by giving the problem of flat side space and interviews. In the problem understanding phase, students perform metacognitive awareness when they rethink a given problem marked by rereading the problem by considering and monitoring things that are important to solve the problem. In the planning phase, students perform metacognitive regulation when they rethink the ways that have been linked to previous learning experiences marked by considering clues to problems that have been connected to the learning experience. In the phase of implementing the plan, students carry out metacognitive evaluations when they think back about the solution that is being worked on by changing and correcting the image that is being made and determining another more appropriate way. In the re-examination phase, students carry out metacognitive evaluation and awareness when they rethink the solutions that have been made marked by rereading the problem and checking the completion from the beginning to the end and convincing themselves that the solutions made are correct.